Comparison of Dental Caries and Gingival Bleeding Status among Diabetic and Non-Diabetic Type 2 Children - Muhammad Afzal, Ali Anwaar, Adeel Ijaz Rana, Fareed Ahmad, Shehnoor Azhar, Saadia Manzar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the dental caries and gingival bleeding status among diabetic and non-diabetic type 2 children Design of the Study: Cross sectional study Study Settings: The current study was conducted in the OPD of Dentistry at the CMH Lahore between the months of January 2021 and June 2021. Material and Methods: A total of 400 children aged 6–18 years enrolled in the research. Children with Type 2 Diabetes Mellitus (T2DM) were included in the study group, whereas children without T2DM were included in the control group (non-diabetic group). Results of the Study: Among non-diabetic subjects, there were 191 (47.8%) males and 209 (52.2%) females respectively and among diabetic subjects, there were 198 (49.5%) males and 202 (50.5%) females respectively. Prevalence of teeth with dental caries among Non-diabetic subjects was found to be 87% (350) whereas among diabetic subjects, it was found to be 93% (371). Conclusion: According to the findings, diabetics were more likely than non-diabetics to have dental caries and periodontal disease. There was a high prevalence of dental caries and missing teeth in diabetic participants, which led to an overall higher mean DMFT score.